Development of Local Economic Potential for Women Through Cracker and Mujair Fish Brains in Dukuh Tunggal Village, Glagah District, Lamongan Regency - Bisri Mustofa; Inayatur Rosyidah; Makhiulil Kirom; Mubasyiroh Mubasyiroh; Mutammimah Putri (Jurnal Indonesia Sosial Teknologi, 2024)
Women who have free time can be used as capital and opportunities to carry out productive activities that can generate income. Dukuh Tunggal Village as the largest area of fish farming in Glagah District has great potential in processing fishery products. women of Dukuh Tunggal Village who are members of the 10 PKK (Family Welfare Development) group try to make crackers and mujair fish brains to increase people's income and welfare. The purpose of this activity is to strengthen the local economic capacity for women in Dukuh Tunggal Village by taking advantage of the business opportunities around them. The implementation method is Asset-Based Community Development (ABCD) which includes three stages, namely the preparation stage, the extension and training implementation stage, and the mentoring stage.